Observation of some parameters on adult millet (Panicum miliaceum L.) individuals by pre-post herbicides controlling mostly grass type annual weeds - Nagy, László (Acta Agraria Debreceniensis, 2010)
The experiment was conducted in warmer mean daily temperature than the many years average, and almost in the same precipitation conditition as the many years average. The herbicides employed were sprayed in the 3-4 leaf stages developing phase of the millet (Panicum miliaceum L.) population by the dose of officially proposed. On the basic of the results, the herbicides didn’t effect deleteriously, in most instances, on the cultur plants in sort and long periodus at all. Tendenciously the values of parameters observed were sligtly better after the Stomp 330EC than the Dual Gold 960EC. ( The values of the parameters are significantly better at the treated variants than the control ones, are in realation with the wheather and development stile of the millet, beside the different weeding status of the plots.)